THE INFLUENCE OF PRODUCT ATTRIBUTES, VALUE PERCEPTIONS, AND CONSUMER EXPERIENCES ON CONSUMER SATISFACTION (STUDY ON UNISBANK SEMARANG STUDENTS) - Andarista Yulian Suryaningrum; Mulyo Budi Setiawan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
This study aims to examine and analyze the effect of product attributes, perceived value and consumer experience on consumer satisfaction at Unisbank Semarang students who are users of wardah products. This study is a descriptive study because it  aims to determine the effect of three independent variables (product attributes, perceived value and consumer experience) on one dependent variable (consumer satisfaction). The population in this study were all Unisbank Semarang students who used Wardah products. Due to the large number of female students, the author only took 100 people in sampling. The data obtained were analyzed by factor analysis method with KMO test and factor loading, instrument reliability test and regression analysis with determinant test, F and T statistical test. The results of this study indicate that product attributes, perceived value and consumer experience have a positive and significant effect on consumer satisfaction.